Self-Perceived Multiple Intelligences of Male and Female - Shahzada, Gulap; Ghazi, Safdar Rehman; Khan, Habib Nawaz; Iqbal, Saiqa; Shabbir, Muhammad Nauman (Richtmann Publishing, 2011)
Intelligence plays a great role in one’s life. This study was conducted with the objective to investigate the differences between self-perceived multiple intelligences of male and female. Results of the study revealed that there is a significant difference between self-perceived verbal/linguistic, logical/mathematical, visual/spatial, interpersonal, and intrapersonal intelligence of the male and female and there is no significant difference between self-perceived musical, bodily/kinesthetic and naturalistic intelligence of the male and female. On the basis of the conclusions it was recommended that students should be explicitly trained and they should provided different opportunities so they may have equal chance for the development of each intelligence, Female should be encouraged to participate in learning activities drawn around logical/mathematical activities, students may be provided both for male and female students with appropriate feed back without discrimination between male and female, Further researches may be conducted to further investigate difference between male and female self-perceived intelligence. Keywords: Multiple Intelligence, IQ, verbal/ linguistic, logical/mathematical, visual/spatial, musica bodily/kinesthetic, interpersonal, intrapersonal, natural.